Severe Hypernatremia as Presentation of Netherton Syndrome - Di Nora, A.; Consentino, M.C.; Messina, G.; Timpanaro, T.; Smilari, P.; Pavone, P. (Global Medical Genetics, 2023)
Netherton syndrome is a rare, multisystem, autosomal recessive genodermatosis characterized by a triad of manifestations: congenital ichthyosis, immune dysregulation, and scalp anomalies. We report the case of a 1-month-old male infant evaluated for failure to thrive and feeding difficulties. At birth, the infant was admitted to intensive care for severe hypernatremia (natremia 186 mg/dL). Upon entering the ward, the general conditions were poor. He presented with diffuse erythrodermia. A dermatological evaluation showed evidence of “invaginated trichuriasis,” a typical sign of Netherton syndrome. Netherton syndrome is caused by a genetic mutation causing loss of function of the SPINK5 gene it encodes for the LEKTI protein, normally expressed in epithelia. Loss of LEKTI induces severe skin barrier defect. The history of the disease is characterized by serious potential complications in the first months of life, such as the risk of hypernatremic dehydration induced by high skin permeability, recurrent and/or severe infections, and growth retardation.
Keywords: hypernatremia; genodermatosis; Trichorrhexis invaginata